Pembelajaran Berdiferensiasi sebagai Langkah Baru dalam Mewujudkan Merdeka Belajar - Sinaga Eka; Tarigan H; Sinurat T; Saragih S; Situmorang M; Saragih L; Prangin Angin P (Journal Innovation In Education, 2024)
Differentiated learning is one strategy that teachers can use to meet the needs of each student. Differentiation is a teaching and learning process where students learn learning materials based on their abilities, what they like, and their individual needs so that they do not get frustrated and feel like failures during the learning process. Teachers must organize learning materials, activities, daily tasks completed in class and at home, and final assessments based on students' readiness to learn the subject matter, interests or what students like to learn, and how to deliver lessons that are in accordance with the learning profile of the students they teach. There are four aspects of differentiated learning that are under the control of the teacher, namely, content, process, product and environment or learning climate in the classroom. Teachers can decide how these four elements will be incorporated into learning in the classroom. Teachers have the ability and opportunity to change the learning environment and climate, as well as the content, process and product of each class based on the student's profile while in the classroom.